The Value of Technology Improvements in Games with Externalities: A Fresh Look at Offsetting Behavior - Michael Hoy; Mattias Polborn (Center for Economic Studies and ifo Institute (CESifo), 2014)
How should we evaluate the welfare implications of improvements to safety technologies in the presence of offsetting behavior? We model this problem as a symmetric game in which each player's payoff depends on his own action and the average action of the other players, and analyze under which conditions an improved technology increases or decreases both the level of precautionary activity and equilibrium utility of players. For mandatory safety technologies, the direction of the welfare effect depends on whether the externality between players is positive or negative, and on whether the improved technology increases the individually optimal activity level, taking the activity of other players as given. For safety technologies that individuals can choose whether to employ, we show that an individual will generally expend too much on reducing the size of loss but, depending on conditions that we specify, either too much or too little on features that reduce the individual's probability of loss.
Keywords: C70; D60; D70; D80; 330